PECULIARITIES OF FEMALE FACTOR IN THE DEVELOP-MENT OF MODERN SOCIETY - Лесін, А. І.; Костенко, Л. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
A long-term experience of investigation and analysis of female factor, including female sexuality, its dependence on the important changes of the society, new matriarchy, which essentially influences upon the life in general sense. Female sexuality as a part of female factor, which unites a lot of functions in women life, is still unfamiliar and uninvestigated. Modern matriarchy with its positive values has great influence on all aspects of human life, including intimate relations, that gratly depend on advantages of sexapill, intelligent women and their partners.